Wednesday

April 16, 2014

April 16, 2014

Posted by **Karlee** on Tuesday, March 26, 2013 at 5:07pm.

f(x)=x^3-2x^2-13x-10

x=

- College algebra -
**Reiny**, Tuesday, March 26, 2013 at 6:01pmf(1) = 1-2-13-10 ≠ 0

f(-1) = -1 - 2 + 13 -10 = 0 , so x+1 is a factor

by synthetic division

x^3 - 2x^2 - 13x - 10 = (x+1)(x^2 - 3x - 10)

= (x+1)(x-5)(x+2) = 0 for roots

x = -1 or x = -2 or x = 5

**Related Questions**

Use the rationals theorem - Use the rationals theorem to find all the zeros of ...

College algebra - Use the rationals theorem to find all the zeros of the ...

college algebra - use the remainder theorem to find the remainder when f(x) is ...

college algebra - use the remainder theorem to find the remainder when f(x) is ...

college algebra - use the rational zeros theorem to find all the real zeros of ...

college algebra - use the rational zeros theorem to find all the real zeros of ...

College algebra - Use the rational zeros theorem to find all the real zeros of ...

college algebra - use rational zeros theorem to find all the real zeros in the ...

College Algebra - Use rational root theorem and the factor theorem to help solve...

College Algebra - Use the rational zeros theorem to find all the real zeros of ...